Amyloid precursor like protein-1 promotes JNK-mediated cell migration in Drosophila. - Wang, X.; Sun, Y.; Han, S.; Wu, C.; Ma, Y.; Zhao, Y.; Shao, Y.; Chen, Y.; Kong, L.; Li, W.; Zhang, F.; Xue, L. (Oncotarget, 2017)
The amyloid precursor like protein-1 (APLP1) is a member of the amyloid precursor protein (APP) family in mammals. While many studies have been focused on the pathologic role of APP in Alzheimer's disease, the physiological functions of APLP1 have remained largely elusive. Here we report that ectopic expression of APLP1 in Drosophila induces cell migration, which is suppressed by the loss of JNK signaling and enhanced by the gain of JNK signaling. APLP1 activates JNK signaling through phosphorylation of JNK, which up-regulates the expression of matrix metalloproteinase MMP1 required for basement membranes degradation and promotes actin remodeling essential for cell migration. Our data thus provide the first in vivo evidence for a cell-autonomous role of APLP1 protein in migration.